Clinico-epidemiological Profile of Sexually Transmitted Infections in a Tertiary Hospital: A Cross-Sectional Study - Karki, Alina; Manandhar, Varsha; Maharjan, Rupak (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Sexually transmitted infections are communicable diseases that occur due to sexual contact. They are a major global health problem that affects the quality of life of patients. Knowledge of the frequency and pattern of sexually transmitted infections helps in early diagnosis and appropriate treatment. The aim of the study was to determine the pattern of various sexually transmitted infections in a tertiary hospital in Kathmandu.Methods: This cross-sectional study was conducted among patients visiting the Dermatology outpatient department of a tertiary hospital in Kathmandu from 1st Dec 2019 to 30th Nov 2023 after ethical approval from the Nepal Health Research Council (Reference Number: 681/2023). The data were retrieved from the records of the department, entered and analyzed using Statistical Package for the Social Sciences version 21.Results: A total of 165 patients were included in the study, among which 121(73.33%) were male and 44(26.67%) were female, with a male-to-female ratio of 2.7:1. Most of the patients were married and in the age group 26 to 35 years. Most common sexually transmitted infections were condyloma acuminata 56(33.95%), urethral discharge syndrome 37(22.43%), herpes genitalis 28(16.97%), vaginal discharge syndrome 20(12.12%), syphilis 18(10.90%), molluscum contagiosum 3(1.81%), and others 3(1.81%).Conclusions: Viral infections were the most common sexually transmitted infections in our study.